Cerebral perfusion alterations and cerebral amyloid in autosomal dominant Alzheimer disease - McDade, Eric (Lippincott Williams & Wilkins, 2014)
OBJECTIVE: To evaluate alterations in cerebral blood flow (CBF) using arterial spin-labeled MRI in autosomal dominant Alzheimer disease (ADAD) mutation carriers (MCs) in relation to cerebral amyloid and compared with age-matched healthy controls. BACKGROUND: Recent work has identified alterations in CBF in elderly subjects with mild cognitive impairment and Alzheimer dementia using MRI. However, similar studies are lacking in ADAD. Subjects with ADAD are generally free of significant vascular disease and offer the opportunity to measure CBF early in the pathologic process before significant symptom onset when unique markers might be identified. METHODS: Fourteen MCs (presenilin-1 and amyloid beta precursor protein) (Clinical Dementia Rating [CDR] 0 = 9, CDR 0.5 = 4, CDR 1 = 1) and 50 controls underwent 3-tesla pulsed arterial spin-labeled MRI. SPM8 was used to test the effect of MC status at the voxel level on CBF before and after controlling for age and CDR. RESULTS: MCs had decreased perfusion in the caudate and inferior striatum bilaterally even after controlling for age and CDR. In MCs, separate areas of decreased CBF were associated with increasing cerebral amyloid and to decreased performance of attention and executive function. CONCLUSIONS: Early CBF changes were identified in asymptomatic and mildly symptomatic subjects with ADAD, particularly in the anterior striatum. Furthermore, amyloid deposition was associated with decreased CBF in a number of regions including anterior and posterior cortical areas. Both amyloid and decreased CBF were associated with declines primarily in executive cognitive function.